2023
DOI: 10.1038/s41598-023-33234-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the effect of water addition on intermolecular interactions of fatty acids-based deep eutectic solvents by molecular dynamics simulations

Abstract: In this work, we focused on the interaction between hydrogen bond acceptor (HBA) and hydrogen bond doner (HBD) in the binary mixtures. The results showed that Cl− anion plays a key role in the formation of DESs. Also, the structural stability of deep eutectic solvents based on fatty acids (FAs) and choline chloride (Ch+Cl−) at different ratios was investigated in water using molecular dynamics simulations. We observed that the interaction between the chloride anion and the hydroxyl group of the cation leads to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The CLX–DES system was able to maintain the supersaturation of CLX for up to 2 h. The fall in the initial supersaturation can be explained from the water-mediated disruption of the hydrogen-bonding network of the DES. The effect of water on the microstructure of DES has been widely studied [ 39 , 40 , 41 , 42 , 43 ], and it was identified that water at high concentrations, owing to its hydrogen bond donor/acceptor property (due to the hydrogen atoms and lone pair of electrons on oxygen atoms, respectively), competes with the DES components to form new hydrogen bonds, leading to a perturbation/disruption in the DES microstructure. However, this effect is not immediate and initiates on crossing a threshold value, which is based on the nature of the DES components and temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The CLX–DES system was able to maintain the supersaturation of CLX for up to 2 h. The fall in the initial supersaturation can be explained from the water-mediated disruption of the hydrogen-bonding network of the DES. The effect of water on the microstructure of DES has been widely studied [ 39 , 40 , 41 , 42 , 43 ], and it was identified that water at high concentrations, owing to its hydrogen bond donor/acceptor property (due to the hydrogen atoms and lone pair of electrons on oxygen atoms, respectively), competes with the DES components to form new hydrogen bonds, leading to a perturbation/disruption in the DES microstructure. However, this effect is not immediate and initiates on crossing a threshold value, which is based on the nature of the DES components and temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The interactions between terpenes and fatty acids in HDESs have been explored through molecular dynamics studies. These studies reveal that strong hydrogen bonds form between the hydroxyl (OH) group of terpenes and the carboxylate oxygen atom of fatty acids, often showing an angular probability distribution of around 150-180 • C [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%